The age of the father is twice the sum of the ages of his two children. After 20 yr, his age will be equal to the sum of the ages of his children. Find the
age of the father.
Let the present age (in year) of father and his two children be x, y and z yr, respectively.
Now by given condition, x=2(y+z) …(i)
and after 20 yr, (x + 20) = (y + 20) + (z + 20)
⇒ y+z +40 = x +20
⇒ y + z = x – 20
On putting the value of (y + z) in Eq. (i) and get the present age of father
x =2(x -20) x
= 2x – 40 = 40
Hence, the father’s age is 40 yr.